1995
DOI: 10.1159/000188713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N<sup>G</sup>-Nitro-<i>L</i>·Arginine Methyl Ester on Nephrotoxicity Induced by Gentamicin in Rats

Abstract: The present experiments were designed to assess the effect of inhibiting NO synthesis on the renal failure induced in rats by treatment with high doses of gentamicin. Eighteen Wistar rats were given gentamicin 100 mg/kg body weight/day for 5 days, whereas another 18 rats were used as control. Half of the gentamicin-treated rats and half of the controls also received the specific inhibitor of NO synthesis, NG-nitro-L-arginine methyl ester (L-NAME), 0.05 mg/ml in the drinking water for 5 days. Arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The inhibition of NO production exacerbates GM nephrotoxicity suggesting that the enhancement of NO production is very important to prevent exacerbation of renal damage in GM-induced nephrotoxicity [37,38]. On the other hand, NO is able to react with O 2 - to produce peroxynitrite anion which itself is very toxic [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of NO production exacerbates GM nephrotoxicity suggesting that the enhancement of NO production is very important to prevent exacerbation of renal damage in GM-induced nephrotoxicity [37,38]. On the other hand, NO is able to react with O 2 - to produce peroxynitrite anion which itself is very toxic [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits all three isoforms of NOS, and experimental data indicate that ADMA produces the expected physiologic changes when infused in vivo (1,13,14). Furthermore, animal models have shown that other NOS inhibitors enhance atherogenesis and promote renal damage consequent upon reduced NO generation (15,16). However, the absolute levels of ADMA and the differences between groups in the current clinical studies are small.…”
mentioning
confidence: 84%
“…Excess NO production has also been reported in gentamicin-induced acute renal failure [38]. However, NO may play a protective role against drug-induced nephrotoxicity as inhibition of NOS by L-NAME has been shown to both aggravate gentamicin-induced renal failure and enhance acute cyclosporin nephrotoxicity [39].…”
Section: Nitric Oxide the Kidney And Renal Diseasementioning
confidence: 99%